Assessment of Methods for Determining Vehicle Emission Characteristics - LASKOWSKI, Piotr; KOZŁOWSKI, Edward; ZIMAKOWSKA-LASKOWSKA, Magdalena; WIŚNIOWSKI, Piotr (Engineering Transactions, 2025)
This paper presents an analysis of pollutant emissions (carbon monoxide, hydrocarbons, nitrogen oxides, methane, non-methane volatile organic compounds and carbon dioxide) from a passenger car, particularly under real-world driving conditions, to more accurately model the impact of transport on the environment. These pollutants were selected due to their regulatory relevance and significant environmental and health impacts. A mathematical model developed in this study was used to estimate emissions, with vehicle speed identified as a key parameter influencing emission levels. Various speed ranges and their impact on emission levels were considered during parametric identification. Since the relationship between pollutants and speed is nonlinear, the least squares method was applied to estimate model parameters for the different pollutants. The model developed in the paper allows for precise emission prediction for various vehicle use scenarios. The scenarios analyzed include urban driving conditions with vehicle speeds not exceeding 60 km/h. The selected speed profile was first recorded in real-world traffic using a portable emissions measurement system (PEMS) and subsequently reproduced on a chassis dynamometer to ensure test repeatability under controlled laboratory conditions.